The effectiveness of Chest Physiotheraphy on Secretory Discharge in Children with Acute Respiratory Infection (ARI) at Ambacang Health Center Padang, Indonesia - Widyastuti, Monna; Ainul Mardiah Sari; Rahmawati (RADINKA JOURNAL OF HEALTH SCIENCE, 2026)
Acute Respiratory Infection (ARI) is the most prevalent disease at the Ambacang Health Center in Padang, with 966 recorded visits and many pediatric patients reporting significant difficulty in expelling phlegm. To address this, a study was conducted using a quasi-experimental design with a one-group pretest-posttest approach to determine the effectiveness of chest physiotherapy. From a population of 59 pediatric patients, 10 respondents were selected via purposive sampling for the study. Data processing involved univariate analysis through descriptive statistics and bivariate analysis using the paired t-test. The results revealed a notable increase in secretion discharge following the intervention; the average amount of secretions released rose from 1–2 ml before treatment to 2.5–4 ml afterward. Statistical analysis yielded a p-value of 0.000, confirming that chest physiotherapy is a highly effective non-pharmacological method for clearing secretions in children with ARI. Based on these findings, it is recommended that the Ambacang Health Center improve its health services by implementing chest physiotherapy as a standard clinical action for respiratory care.